Novel Biomarkers of Health and Degeneration in Human Intervertebral Discs: In-depth Proteomic Analysis of Collagen Framework of Fetal, Healthy, Scoliotic, Degenerate, and Herniated Discs - Shanmuganathan Rajasekaran; Dilip Chand Raja Soundararajan; Sharon Miracle Nayagam; Chitraa Tangavel; Muthuraja Raveendran; KS Sri Vijay Anand; Ajoy Prasad Shetty; Rishi Mugesh Kanna (Asian Spine Journal, 2023)
Study Design Profiling proteins expressed in the nucleus pulposus (NP) of intervertebral discs (IVDs) in five different biological states. Purpose To evaluate the molecular complexity of the collagen (COL) framework and its role in the health and disease of human IVDs. Overview of Literature Changes in COL composition have been linked to degenerative disk disease (DDD). Despite the fact that humans have 28 different types of COLs, most of the literature focuses solely on COL-1 and COL-2. This study used high-end proteomic technology to examine the entire COL composition of the human IVD across fetal (developmental-FD), normal (healthy-ND), scoliotic (early degeneration-SD), herniated (degenerate-DH), and degenerated (DD) disk phenotypes. Methods Forty NP tissues were snap-frozen in liquid nitrogen (−196°C) immediately before being subjected to proteomic and bioinformatic analyses from five different disk phenotypes (eight each). Results Tandem mass spectrometric analysis revealed a total of 1,050 proteins in FDs, 1,809 in ND, 1,487 in SD, 1,859 in DH, and 1,538 in the DD group. Of 28 major collagens reported in the human body, this study identified 24 different collagens with 34 subtypes in NP. Fibril-forming collagens (COL-1, 2, and 11A1) and fibril-associated collagens with interrupted triple helices (COL-9A1, 12A1, and 14A1) were abundantly expressed in FDs, representing their role in the development of NP. Multiplexin (COL-15), a hybrid proteoglycan–collagen molecule, was discovered only in FDs. Degeneration was associated with COL2A1 downregulation and COL-10A1 upregulation. Conclusions COL10 was discovered to be a new biomarker for disk degeneration. Besides COL-1 and 2, other important COLs (6, 9, 11, 12, 14, 15) with anabolic potential and abundant expression in the fetal phenotype could be investigated for tissue engineering and novel DDD therapy.